If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -10 = -9 + -3y + -8y Reorder the terms: -10 + 5y = -9 + -3y + -8y Combine like terms: -3y + -8y = -11y -10 + 5y = -9 + -11y Solving -10 + 5y = -9 + -11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11y' to each side of the equation. -10 + 5y + 11y = -9 + -11y + 11y Combine like terms: 5y + 11y = 16y -10 + 16y = -9 + -11y + 11y Combine like terms: -11y + 11y = 0 -10 + 16y = -9 + 0 -10 + 16y = -9 Add '10' to each side of the equation. -10 + 10 + 16y = -9 + 10 Combine like terms: -10 + 10 = 0 0 + 16y = -9 + 10 16y = -9 + 10 Combine like terms: -9 + 10 = 1 16y = 1 Divide each side by '16'. y = 0.0625 Simplifying y = 0.0625
| 3x/7=1/11 | | -5-15y+1=2(7y-16) | | 3-/8x-6/=3 | | (3x-7)(x)=120 | | 3x+9y=27solvey | | 11.2=v/7 | | 10x-12x=20 | | 17v=9v+48 | | x^3-10x^2+17x-8=0 | | 4x-7=2y+5 | | 15x+10=6x+298 | | -5-15y+1=2(7y-16)-y | | X-1/6=7/12 | | 10x-12x-8=12 | | 3x-2=2x(-6) | | -114q=-1176-16q | | A=18W-W^2 | | ix-3x=0 | | 2(x-4)=3x-9-x | | y-2=4/5(x-3) | | (2x-1)(5x-5)= | | 4r-4=(r-4)(r-4) | | 0.6x-1.9y+3.2=0 | | 160=3x+y | | -9y+19=4y-7 | | 1-4.9x^2=0 | | (w-4)/4w=1/5 | | 12y-7+1+4y= | | ix=3x | | 7-2y=10-6y+4y | | x(x-3)=16/3 | | -3(5u-2)+5u=4(u+4) |